Negative Thermal Expansion in the Materials With Giant Magnetocaloric Effect - Hu, Fengxia; Shen, Feiran; Hao, Jiazheng; Liu, Yao; Wang, Jing; Sun, Jirong; Shen, Baogen (Frontiers in Chemistry, 2018)
Negative thermal expansion (NTE) behaviors in the materials with giant magnetocaloric effects (MCE) have been reviewed. Attentions are mainly focused on the hexagonal Ni2In-type MM'X compounds. Other MCE materials, such as La(Fe,Si)13, RCo2, and antiperovskite compounds are also simply introduced. The novel MCE and phase-transition-type NTE materials have similar physics origin though the applications are distinct. Spin-lattice coupling plays a key role for the both effect of NTE and giant MCE. Most of the giant MCE materials show abnormal lattice expansion owing to magnetic interactions, which provides a natural platform for exploring NTE materials. We anticipate that the present review can help finding more ways to regulate phase transition and dig novel NTE materials.